Embodied Cognition or Abstract Representation? Testing Competing Accounts of Transparent and Opaque English Idiom Learning through Augmented Reality (Al-Farooq Journal of Sciences, 2026)
This study compared two theories of idiom learning embodied cognition and abstract representation to examine how augmented reality (AR) affects the learning of transparent and opaque English idioms by Libyan EFL undergraduate students. A true experimental 2 × 2 mixed factorial design was used, with Learning Approach (embodied AR vs. abstract instruction) as the between-subjects factor and Idiom Type (transparent vs. opaque) as the within-subjects factor. A total of 108 students at B1–B2 proficiency levels were randomly assigned to one of two groups using concealed allocation. The embodied group learned 30 idioms through a marker-based AR application that presented 3D animated scenes and interactive learning experiences. The abstract group used the same application but received only definitions, translations, and example sentences without animation or interaction. Students were tested on idiom recognition, interpretation, and production immediately after instruction and again four weeks later. Mixed ANOVA results for the immediate post-test showed a significant interaction between learning approach and idiom type. The embodied AR group performed much better than the abstract group on opaque idioms (p < .001, d = 1.74, 95% CI [1.38, 2.10]), while the difference for transparent idioms was small. ANCOVA controlling for pre-test scores produced the same pattern of results. The delayed post-test showed that students who learned through embodied AR retained opaque idioms better over time. Confirmatory factor analysis using lavaan supported the validity of the research instruments. Assumption checks and Bayesian sensitivity analyses further confirmed the reliability of the findings. Overall, the results indicate that opaque idioms benefit greatly from sensory-motor learning experiences, supporting the embodied cognition account, whereas transparent idioms can be learned effectively through traditional symbolic instruction.
Keywords: embodied cognition; abstract representation; idiom learning; augmented reality; Libyan EFL; opaque idioms; mixed ANOVA; Bayesian analysis; reproducible research